The fungal effect of benomyl and phenolazoline in fungi and the production of cellulose enzyme and single cell protein Trichoder1na viride - Raghed Al-Azzo; Reyadh Al-Barhawi (College of Education for Pure Sciences, 2007)
This study was conducted aiming to obtain an efficient fungal isolate in cellulase and single cell protein production from a local isolate Trichoderma viride by the mutation effect of Benomyl and Vinclozolin. It was found that Benomyl has a lethal effect on the isolate at all concentrations of the fungicide and spores suspension used, at the same time it was found that Vinclozolin has an obvious mutational effect on the parental isolate at the concentration 2.0 mg active material/ml of standard medium, the parental isolate showed clear morphological changes in colony shapes, colors, ability for growth in addition to the profound changes in fungal mycelia which was confirmed by the application of slide culture technique. A qualitative and quantitative tests have been carried out to explore the efTiciency of the new mutant for cellulase and single cell protein lJroduction in solid and liquid media, it achieved cellulase specific activity and single cell protein (3 .604 micromole/min/mgm protein and 29.4 74% protein in dry weight) respectively.